Autumn : disintegration - Moody, David, 1970- (St. Martin's Griffin, 2011)
"Forty days have passed since the world died. Billions of corpses walk the Earth. Everything is disintegrating... A group of eleven men and woman have survived against the odds. On almost a daily basis, they attack the dead with brutal ferocity, tearing through them with utter contempt. Somewhere nearby, out of sight and out of earshot, are another group who have adopted a completely different survival strategy. Where the others have used brutality and strength, these people have demonstrated subtlety, planning and tactics. A series of horrific events force the two groups together. Backed into a corner and surrounded by hundreds of thousands of corpses, they all know that their final battle with the dead is about to begin. Do they attack first, or is it time to take a different approach? The decision splits the group, and with the lives of everyone at stake, no-one is prepared to back down. Time is running out, and it's no longer clear whether the biggest threat comes from outside the walls of the shelter or from within"--